Analysis of Path Matrix Based on Precedence Diagram Using Ranked Positional Weight Method - Wiki Sabardi (Fakultas Teknik Universitas Samudra, 2022)
Line balance problems are common in both the assembly and manufacturing industries. This is evidenced by the fact that some workstations have relatively high work congestion, less than Suboptimal line efficiency and non-smooth process flow this research is to: determine the line balancing by making the best path matrix based on the division of workstations. This study uses the Helgeson-Birnie method. This research resulted in design results of line efficiency of 89.16%, idle time of 2683.64, transient delay of 10.84%, smoothness index of 843.88, and 15 workstations. Based on special calculations for changes in the smoothness value, there is a decrease in the smoothness index value from 2041.72 to 843.88.